Hydrogels and nanogels: effectiveness in dermal applications - Jéssica da Cruz Ludwig; Diana Fortkamp Grigoletto; Daniele Fernanda Renzi; Wolf-Rainer Abraham; Daniel de Paula; Najeh Maissar Khalil (Beilstein Journal of Nanotechnology)
Drug delivery systems (DDSs) are an important tool for obtaining medicines with improved physicochemical properties, especially for drugs with stability, absorption, and biodistribution impairments. Among the DDSs, we can highlight hydrogels and nanogels, which are easy to obtain, show good biocompatibility, and have several applications in the design of drug carriers for dermal and ocular administration. In this review, we introduce a brief concept on hydrogels, underlining compounds such as chitosan and alginate, and methods used for their preparation. Nanogels, with their attractive features, such as high drug encapsulation and penetration enhancer embedding, are also addressed. Finally, the application of these systems in dermal pathophysiological processes through the incorporation of drugs for enhancing skin permeation brings out promising prospects for innovation which may arise in the drug delivery field.